2021
DOI: 10.1042/etls20200339
|View full text |Cite
|
Sign up to set email alerts
|

The Y chromosome and its use in forensic DNA analysis

Abstract: Originally relatively ignored in forensic investigations because its genetic analysis lacks inference of individual identification, the value of Y chromosome analysis has been proven in cases of sexual assault, particularly where the amount of material left by a male assailant is limited in comparison with female DNA. All routine analysis of autosomal DNA, however, targets a gene (AMELY) on the Y chromosome in order to identify the sex of the DNA source and this is discussed in the context of the genetic struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, it has been observed that the inclusion of more loci does not compensate for the absence of genetic information from the mother or the father [35,40,[42][43][44]. The use of Y-chromosome STRs can help only when the victim is male, and the possibility that a close relative of the putative father is the biological father cannot be ruled out [45]. X-chromosome STRs must be analyzed along with other genetic markers to obtain useful data and can only be used with accuracy when the victim is female, as there are no X-chromosome alleles inherited by descent in a father-son relationship [46].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been observed that the inclusion of more loci does not compensate for the absence of genetic information from the mother or the father [35,40,[42][43][44]. The use of Y-chromosome STRs can help only when the victim is male, and the possibility that a close relative of the putative father is the biological father cannot be ruled out [45]. X-chromosome STRs must be analyzed along with other genetic markers to obtain useful data and can only be used with accuracy when the victim is female, as there are no X-chromosome alleles inherited by descent in a father-son relationship [46].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent review articles were published on forensic applications of Y-chromosome testing [ [444] , [445] , [446] ]. As discussed previously in Section 1.2 , an ISFG DNA Commission summarized the state of the field with Y-STR interpretation [ 39 ].…”
Section: Emerging Technologies Research Studies and Other Topicsmentioning
confidence: 99%
“…In real‐case scenarios, depending solely on Y‐STR is far from enough. This means that even if there was a 100% Y‐STRs match between a sample and a suspect, we cannot differentiate the contributor from his patrilineal lineages [ 6 , 8 ]. To address this problem, scientists worked hard and discovered new Y‐STRs with high mutation rates, called rapidly mutating (RM) Y‐STRs.…”
Section: Introductionmentioning
confidence: 99%